Research in compulsory drug detention centres in China: Characteristics and ethical considerations - Yazid Barhoush; Joseph J. Amon (Global Public Health)
More than 500 centres in China hold over 300,000 individuals in what has been described by the United Nations as unethical and ineffective compulsory treatment and rehabilitation centres. Individuals in these centres face widespread human rights abuses, including lack of due process, forced labour, physical and sexual violence, and denial of healthcare. Because of the vulnerability of individuals in detention settings to abuse in research trials, ethical guidelines have required research to pose no more than minimal risk, to address the process of incarceration, and the health or well-being of detained individuals. To understand the scope and ethical protections of research conducted in Chinese drug detention centres, we conducted a literature review by searching the China Academic Journals Database for Chinese language research articles published between 2012-2021. We identified 68 articles of drug detention detainees that examined physical and psychosocial health; infectious disease prevalence; past drug use; and other topics. The majority of studies (56%) did not provide any information on the consent of research participants. Only ten (15%) studies reported receiving ethics approval. No studies examined the process or conditions of detention. Journal editors, in China and globally, should increase scrutiny of research conducted in compulsory drug detention settings.